2014
DOI: 10.1177/0016986214547636
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Attitudes to Gifted Programs/Provisions

Abstract: This study investigated whether a number of cultural orientation, sociodemographic, academic achievement, and personal/ personal experience variables predict attitudes toward the provision of special programs/provisions for gifted students. Surveys completed by 241 Australian preservice teachers were analyzed using confirmatory factor analyses and multiple regression analyses. The findings suggest that (a) low power distance orientation, contact with gifted persons, and older age predict support for special gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 48 publications
0
33
1
2
Order By: Relevance
“…Mandatory modules on the education of the gifted that provide a setting in which teachers learn about conceptions of giftedness and can reflect on their stereotypes should be integrated in their curriculum. Several studies on teachers' attitudes towards the education of the gifted showed that stereotypes can be changed through information transfer and contact (e.g., Goodnough, 2001;Jung, 2014;Lassig, 2009;Plunkett & Kronborg, 2011). Whether such modules also have an effect on stereotypes about giftedness and gender still needs to be explored: For example, by comparing teachers who participated in a module on teaching gifted girls and boys, and learning about giftedness and its implications and teachers who did not.…”
Section: Implications For Practicementioning
confidence: 99%
“…Mandatory modules on the education of the gifted that provide a setting in which teachers learn about conceptions of giftedness and can reflect on their stereotypes should be integrated in their curriculum. Several studies on teachers' attitudes towards the education of the gifted showed that stereotypes can be changed through information transfer and contact (e.g., Goodnough, 2001;Jung, 2014;Lassig, 2009;Plunkett & Kronborg, 2011). Whether such modules also have an effect on stereotypes about giftedness and gender still needs to be explored: For example, by comparing teachers who participated in a module on teaching gifted girls and boys, and learning about giftedness and its implications and teachers who did not.…”
Section: Implications For Practicementioning
confidence: 99%
“…Teachers' attitudes toward gifted education have intrigued many researchers (e.g., Bégin, & Gagné, 1994;Cross, Cross, & Frazier, 2013;Jung, 2014;Lassig, 2009;McCoach & Siegle, 2007;Tallent-Runnels, Tirri, & Adams, 2000;Tirri, Tallent-Runnels, Adams, Yuen, & Lau, 2002;Tirri & Uusikylä, 1994;Troxclair, 2013). This area has been regarded as an important one to study, since it is widely assumed that teachers should have appropriate attitudes toward the gifted in order to address gifted students' needs effectively (Lassig, 2003;Troxclair, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In a similar vein, a lack of experience with gifted learners is associated with perceptions of gifted education programs as elitist and unnecessary (Jung, 2014). One concerning finding regarding preservice teacher perceptions of giftedness came from Bain et al's (2007) study on 210 undergraduate teaching candidates.…”
Section: Deficit Thinking and Teacher Expectationsmentioning
confidence: 99%
“…The potential consequence of this mentality is that students who do not display such characteristics are less likely to be considered by teachers as gifted or as having gifted potential. Research on training that works to challenge narrow conceptions of giftedness highlights two important findings: First, preservice teachers have been found to view gifted individuals in a more positive light and demonstrate an increased understanding that advanced learners have unique needs when they have had previous involvement with gifted individuals (Berman et al, 2012; Jung, 2014). Second, perceptions are more likely to change when the training received is hands‐on and requires direct application or immersive experience (Bangel, Moon, & Capobianco, 2010; Berman et al, 2012).…”
Section: Deficit Thinking and Teacher Expectationsmentioning
confidence: 99%